Sensitive detection of hydroxymethylcytosine levels in normal and neoplastic cells and tissues. Issue 9 (14th February 2019) - Krais, Annette M.; Park, Yoon Jung; Reifenberger, Guido; Meister, Michael; Plass, Christoph; Schmeiser, Heinz H.
Abstract: A new sensitive analytical method using capillary electrophoresis with laser induced fluorescence (CE‐LIF) was applied for the simultaneous detection of DNA methylation and hydroxymethylation levels in human cancers of different origin. DNA hydroxymethylation, measured as 5‐hydroxymethylcytosine (5hmC) levels, was decreased in gliomas with mutation in the isocitrate dehydrogenase 1 ( IDH1 ) gene when compared to IDH1 ‐wildtype gliomas. Independent from IDH1 mutation, 5hmC levels were decreased in lung carcinomas when compared to normal lung tissue. Reduced DNA hydroxymethylation was also observed upon dedifferentiation in cultured murine embryonic fibroblasts. Our data show that reduced DNA hydroxymethylation is related to cellular dedifferentiation and can be detected in various types of cancers, independent from the IDH1 mutation status. Quantitative determination of altered 5hmC levels may therefore have potential as a biomarker linked to cellular differentiation and tumorigenesis.